The Influence of Digital Leadership Style and Career Development on Employee Performance Through Organizational Commitment ( Study at the General Election Commission of Bali Province) - I Wayan Budiarta; I Putu Santika; I Ketut Mustika (PT Mattawang Mediatama Solution, 2024)
The purpose of this research is to determine the influence of digital leadership style and career development on organizational commitment at the General Election Commission of Bali Province, to determine the influence of digital leadership style, career development and organizational commitment on the performance of employees of the General Election Commission of Bali Province, and to classify the role of organizational commitment in mediating the influence of digital leadership style and career development on the performance of Bali Province General Election Commission employees. The total population in the study was 44 employees at the Bali Province KPU. The sampling technique used was saturated sampling, so the number of samples used was 44 people. Data analysis in this study used the Partial Least Square (PLS) test. The results of the analysis show that digital leadership style and career development have a positive and significant effect on organizational commitment at the General Election Commission of Bali Province, then digital leadership style, career development and organizational commitment have a positive and significant effect on the performance of employees of the General Election Commission of Bali Province, as well as organizational commitment able to partially mediate the influence of digital leadership style and career development on employee performance